PENGARUH METODE CHAIN WRITING TERHADAP KETERAMPILAN MENULIS TEKS PERSUASI SISWA KELAS VIII MTS NURUL ISLAM INDONESIA BARU TAHUN AJARAN 2023/2024 - Diza Afrillia; Salmah Naelofaria (Jurnal Bastra (Bahasa dan Sastra), 2025)
The purpose of this study was to examine the effect of the chain writing learning method on the skills of writing persuasive texts by class VIII students of Mts Nurul Islam Indonesia. The population of this study was all class VIII students of MTs Nurul Islam Indonesia, with a total of 64 students. The sample used was class VIII-2 students as a control class totaling 21 students and VIII-3 as an experimental class totaling 21 students. This study used an experimental method with a post-test only control group design. Data analysis was carried out using the control class and experimental class analysis requirements test, the normality test of the control class and experimental class and hypothesis testing. The results showed that the average post-test score in the control class was 52.85 which was in the very poor category, while the average post-test score in the experimental class was 80 which was in the good category. Based on the results of the study and the "t" test (4.27> 1.720), the null hypothesis (H_0) was rejected and the alternative hypothesis (H_a) was accepted. The results of the study showed that the use of the chain writing method had an influence on the skills of writing persuasive texts by class VIII students of MTs Nurul Islam Indonesia in the 2023/2024 academic year.